Mine value chain inefficiencies and their impact on ore accounting and reconciliation -Orapa Diamond Mine - Dihutso, Baboloki (My University, 2021)
The mining industry is faced with unprecedented challenges, from operational constraints to the market end. There is a need to monitor the areas of concern more closely and address them with corrective measures especially where the mining operations teams can exercise control. Such concerns were investigated and the value-eroding activities along the mine value chain at Orapa mine were identified. Furthermore, a relationship between operational processes and the reserve carat ratio (RvCR), as a performance indicator for the mine’s major assets (mineral resource estimate and plants), was established. The objective of this research was to ultimately provide recommendations that would help generate shareholder value at Orapa, Letlhakane and Damtshaa Mines (OLDM) along the mine value chain. These recommendations ,after analysis of scientific observations, would be administered through optimised ore accounting, reconciliation and reporting. This study identified that there was room for improvement in the areas of mineral resource estimation, drilling and blasting, loading and hauling, and recovery. Pivotal to these observations, the Reconcilor Reporting System (Reconcilor) was utilised as part of reporting the mineral resource accounting and reconciliation at Orapa mine. Reconcilor, together with survey data and Wenco Database, form the hub for ore accounting, reconciliation and reporting. The RvCR is a key indicator that also forms part of the report outputs. Both operational and system shortcomings or inefficiencies have been acknowledged, appraised and the findings outlined. The focus of the study was on how the inefficient activities along the mine value chain impact the RvCR and how they could be managed to create shareholder value. In line with this statement, several recommendations were offered.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2021